SEMANGAT AGGIORNAMENTO DAN MISI DALAM DEVOSI HATI KUDUS YESUS MENURUT ARNOLDUS JANSSEN - Ian Jovi Sianturi; Antonius Denny Firmanto; Nanik Wijiyati Aluwesia (Lembaga Penelitian STKIP Widya Yuwana, 2022)
The Devotion to the Sacred Heart of Jesus is a spiritual treasure of the Church that can help the growth of people's faith and for the implementation of the work of proclaiming the Gospel for all nations. Arnold Janssen who has an extraordinary missionary spirit introduced the devotion of the Sacred Heart of Jesus to the world. His devotion is not just an adoption from his predecessors but also carries a distinctive spirit, missionary spirit, and openness. In the spirit of the Second Vatican Council, it is called an aggiornamento. This article aims to explore the spirit of renewal and the spirit of missionary work. The method used by the author in this search is a literature study. Through this analysis, the writer finds that the spirit of “aggiornamento” is also present in the devotion of the Sacred Heart according to Arnold Janssen. The contribution from the spirit of spiritual life and motivation introduced by Arnold through the devotion to the Sacred Heart of Jesus is very useful for the preaching and pastoral work of the Church. This devotion introduced by Arnold can also be one of the relevant means of preaching and pastoral of the Church.